Actualisation of Qasim Amin's Emancipation Ideas in the Digital Age: A Case Study Analysis of Muslim Women Travellers - Novi Andini (Averroes: Journal for Science and Religious Studies, 2026)
Research Background: This article examines the actualization of Qasim Amin’s concept of women’s emancipation in the phenomenon of Muslim women travelers in the digital era. The study addresses the question of how Muslim women negotiate religious identity, freedom, and digital mobility while engaging in public and economic spaces through social media. Methods: Using a qualitative approach with a case study design, data were collected through digital documentation, observation of social media content, and literature review, and analyzed using content analysis within the framework of Islamic feminism and Amin’s thought. Key Findings: The findings show that Muslim women travelers represent a contemporary form of emancipation characterized by autonomy, digital literacy, economic independence, and the creative integration of piety with modern lifestyles. Their activities demonstrate that religiosity does not hinder emancipation but can function as an ethical foundation for agency and social participation. Contribution: This article contributes theoretically by contextualizing Qasim Amin’s ideas within digital culture and empirically by highlighting everyday practices of emancipation in virtual spaces. Conclusion: It concludes that women’s emancipation in Islam is a dynamic and evolving process, shaped by technology and socio-economic transformation, rather than a departure from religious values.